Interspecies violence and crimes of dissent: communication ethics and legitimacy in message crimes involving wildlife - Essen, Erica von (Critical criminology, 2017)
In this article, we consider the phenomenon of message crimes involving harm to wildlife from a sociological and criminological perspective. Using a case study of dissident Nordic hunters killing protected wolves to send a message to the state agencies responsible for their conservation, we engage philosophically with the question of wildlife victimhood and why interspecies violence is unjustifiable as a mode of political dissent. As an alternative to the species justice perspective in green criminology, we examine how the acts disrespect animals as moral subjects of public communication and frustrate dialogue regarding what is owed to them in terms of political justice.